Implementation of A-Star Algorithm In Finding The Shortest Route of Cooking Oil Distribution in Karo Regency Using Graph - Ropiqoh, Ropiqoh; Lubis, Riri Syafitri (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2023)
PT. XYZ is a company that distributes cooking oil in Karo Regency. Based on what has been observed at PT. XYZ, the distribution of goods has not contained standard provisions in determining the route of delivery of goods, large areas cause great difficulties in the distribution of goods because they require greater transportation costs. To overcome the distribution problem, a workable solution is the A-Star algorithm using graphs. The A-Star algorithm has two points, namely Open List and Close List.  Where conceptually open list means a point that can be skipped while close list means a point that cannot be passed. And usability the Close List is needed so that the algorithm does not need to check the points it passes, so that it can more quickly complete the search process and the checking process at each point can be less, In general, the concept of determining the closest path in an algorithm is that it can stop when the open list is not found and the endpoint has been obtained. while the company's route was 30.95 km. Then the percentage of mileage savings is 62.16%. This shows that the A-Star algorithm can minimize distance and also save companies costs.